PENERAPAN MEDIA BANDICAM DENGAN PENDEKATAN REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN PAI KELAS XI IPS DI SMA NEGERI PLANDAAN JOMBANG - Khotimah, Khusnul; Hasanah, Faridatul (Universitas KH. A. Wahab Hasbullah, 2021)
This research is motivated by the existence of student learning outcomes in PAI (Islamic Religious Education) lessons which are under KKM, so the author took the initiative to research and propose solutions by applying bandicam media. The purpose of this study was to describe the improvement of student learning outcomes by applying bandicam media with a realistic approach to PAI lessons in class XI at Plandaan State Senior High School Jombang. This type of research is classroom action research with research subjects in class XI IPS 3 SMA Negeri Plandaan, and the object of this research is the use of videos recorded through the bandicam application to improve student learning outcomes in PAI lessons. The research was conducted from March 1 to March 31, 2021. The action was carried out in two cycles, each cycle consisting of one meeting. The research procedure includes planning, implementation, observation, and reflection. The results showed a significant increase. Data collection techniques using tests, observations, and documentation. While the data analysis technique used descriptive qualitative data analysis method. The average score obtained at the end of the first cycle was 69.82 with the number of students who reached the KKM as many as 21 students (63.64%), then at the end of the second cycle the average score of students increased to 80.30 and as many as 31 students ( 93.94%) obtained a score of reaching the KKM.